Being, Science and Logic in the Golden Age - Redmond, Walter (1996)
Spanish and Spanish-American logicians of the 16th and 17th centuries worked with a complex "theory of types"to account for the various kinds of beings denoted or signified in language. A. de la Vera Cruz and his colleagues supposed a many-sorted logical system where general sentences are reducible to strings of identities whose terms refer to singular things and which lend themselves to basic semantic analysis.A. Rubio worked out a theory of scientific language and applied it to logic itself, defining propositions of logic as attributions of second-ordermental relational properties to first order contents, themselves attribut able to singular objects.